Ingresos fiscales y elasticidades tributarias: estimación de las elasticidades tributarias de corto y largo plazo para los principales impuestos - Conejo Fernández, Carlos (2013)
The main objective of the article is to provide a measuring of the elasticities of the main taxes of the Costa Rican tax system, so that it allows giving signs about the effects that can be perceived according to the cycles of economy and that it contributes to the analysis of the fiscal situation of the country. The estimates of the elasticities are obtained through the implementation of a model of regression, estimating the elasticities of short and long-term. The tax elasticities measure the change that tax incomes undergo in view of the changes in the income or national production. If the collection depends on several factors, the most important is to determine to which factor is useful to calculate its elasticity, at the same time, it must be taken into account that the value of the elasticity depends on basically of the tax structure and of the progressiveness of the system. The elasticity of the tax collection is a variable of great importance in the analysis of the tax evolution and for the projections of tax incomes.